Party at Émile Benoit’s house. Gordon Benoit playing the guitar - Cox, Pauline (1992)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « A Field Trip to Black Duck Brook: Nov. 11-15 1992. Interview with Tommy Formanger of Black Duck Brook. Nov. 14 1992 ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "A Field Trip to Black Duck Brook: Nov. 11-15 1992. Interview with Tommy Formanger of Black Duck Brook. Nov. 14 1992".